Stringent monitoring can decrease mortality of immune checkpoint inhibitor induced cardiotoxicity - Wang, Ying; Ertl, Carolin; Schmitt, Christina; Hammann, Linda; Kramer, Rafaela; Grabmaier, Ulrich; Schöberl, Florian; Anz, David; Piseddu, Ignazio; Pesch, Giulia; Vera, Julio; Froehlich, Waltraud; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Immune checkpoint inhibitor (ICI)-induced myocarditis is a rare immune-related adverse event (irAE) with a fatality rate of 40%–46%. However, irMyocarditis can be asymptomatic. Thus, improved monitoring, detection and therapy are needed. This study aims to generate knowledge on pathogenesis and assess outcomes in cancer centers with intensified patient management. Methods Patients with cardiac irAEs from the SERIO registry (www.serio-registry.org) were analyzed for demographics, ICI-related information (type of ICI, therapy line, combination with other drugs, onset of irAE, and tumor response), examination results, irAE treatment and outcome, as well as oncological endpoints. Cardiac biopsies of irMyocarditis cases (n = 12) were analyzed by Nanostring and compared to healthy heart muscle (n = 5) and longitudinal blood sampling was performed for immunophenotyping of irMyocarditis-patients (n = 4 baseline and n = 8 during irAE) in comparison to patients without toxicity under ICI-therapy (n = 4 baseline and n = 7 during ICI-therapy) using flow cytometry. Results A total of 51 patients with 53 cardiac irAEs induced by 4 different ICIs (anti-PD1, anti-PD-L1, anti-CTLA4) were included from 12 centers in 3 countries. Altogether, 83.0% of cardiac irAEs were graded as severe or life-threatening, and 11.3% were fatal (6/53). Thus, in centers with established consequent troponin monitoring, work-up upon the rise in troponin and consequent treatment of irMyocarditis with corticosteroids and –if required–second-line therapy mortality rate is much lower than previously reported. The median time to irMyocarditis was 36 days (range 4–1,074 days) after ICI initiation, whereas other cardiotoxicities, e.g. asystolia or myocardiopathy, occurred much later. The cytokine-mediated signaling pathway was differentially regulated in myocardial biopsies as compared to healthy heart based on enrichment Gene Ontology analysis. Additionally, longitudinal peripheral blood mononuclear cell (PBMC) samples from irMyocarditis-patients indicated ICI-driven enhanced CD4+ Treg cells and reduced CD4+ T cells. Immunophenotypes, particularly effector memory T cells of irMyocarditis-patients differed from those of ICI-treated patients without side effects. LAG3 expression on T cells and PD-L1 expression on dendritic cells could serve as predictive indicators for the development of irMyocarditis. Conclusion Interestingly, our cohort shows a very low mortality rate of irMyocarditis-patients. Our data indicate so far unknown local and systemic immunological patterns in cardiotoxicity.